2012
DOI: 10.1016/j.rmed.2011.12.017
|View full text |Cite
|
Sign up to set email alerts
|

HIV and asthma, is there an association?

Abstract: Summary Objective To evaluate whether asthma and airway hyper-responsiveness are associated with HIV infection. Methods We reviewed the literature on HIV-associated pulmonary diseases, pulmonary symptoms, and immune changes which may play a role in asthma. The information was analyzed comparing the pre-HAART era to the post-HAART era data. Results HIV-seropositive individuals commonly experience respiratory complaints yet it is unclear if the frequency of these complaints have changed with the initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Amongst children and adolescents living with HIV, the history of rhinitis was estimated at 60% [ 19 ]. Asthma was also considered a disease of high incidence and prevalence among children and adolescents living with HIV, according to other studies [ 22 - 24 ]. Regarding skin manifestations of HIV infection, eczema has been reported as a rather frequent disease among adults and children [ 25 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst children and adolescents living with HIV, the history of rhinitis was estimated at 60% [ 19 ]. Asthma was also considered a disease of high incidence and prevalence among children and adolescents living with HIV, according to other studies [ 22 - 24 ]. Regarding skin manifestations of HIV infection, eczema has been reported as a rather frequent disease among adults and children [ 25 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum IgE levels in HIV infection were recognized early in the AIDS epidemic, [81][82][83] but the relationship between these levels and asthma in HIV infection has not been extensively studied. In the study by Poirier and colleagues, more HIV-infected men had elevated total serum IgE levels compared with a control population (38% [95% CI: [32][33][34][35][36][37][38][39][40][41][42][43][44] vs. 26% [95% CI: [21][22][23][24][25][26][27][28][29][30][31]; no p-value provided).…”
Section: Hiv Infection and Markers Of Atopymentioning
confidence: 99%
“…Recent cohort studies have demonstrated a rise in asthma incidence following antiretroviral therapy (ART) in US children living with HIV [1][2][3], possibly due to immune reconstitution [2]. As the extent of immune reconstitution can be affected by the pre-ART CD4 level, we assessed new onset asthma in a randomized study of children who initiated ART at different CD4 levels in the Pediatric Randomized Early versus Deferred Initiation in Cambodia and Thailand study (The PREDICT study) [4].…”
mentioning
confidence: 99%
“…inhaled budesonide, unspecified oral/inhaled bronchodilator, and salbutamol + budesonide) (12.5%). Median (IQR) durations of medications use were 16 (10-41) days for salbutamol, 7 [5][6][7][8] days for terbutaline, 167 (34-427) days for budesonide, and 5 [2][3][4][5][6] days for bronchodilator with no differences between arms (all p N 0.2).…”
mentioning
confidence: 99%